Stereoselective Synthesis of Glycosyl Cyanides by TMSOTf‐Mediated Ring Opening of 1, 6‐Anhydro Sugars. Issue 5 (8th January 2023) - Liang, Yan; Laporte, Adrien G.; Bodlenner, Anne; Compain, Philippe
Abstract: We describe herein a convenient access to glycosyl cyanides by way of TMSCN ring opening of 1, 6‐anhydro sugars mediated by TMSOTf with modest to high stereocontrol in the D‐ gluco, D‐ galacto and D‐ manno series. The reaction is tolerant to various functional groups including free alcohols, alkenes and terminal alkynes. The straightforward synthesis of a constrained analogue of 1‐cyano‐D‐glucal with a 3, 6‐anhydro sugar framework is presented to illustrate the interest of the TMSCN ring‐opening reaction. Abstract : The stereocontrolled TMSOTf‐ring opening of 1, 6‐anhydrosugars with TMSCN leading to glycosyl cyanides is presented as well as an application to the straightforward synthesis of a conformationally‐constrained analogue of 1‐cyano D‐glucal.